Gamma probe-guided confirmation of balloon placement in endovascular procedures. Issue 6 (June 2019) - Park, Yunchul; Jo, Young Goun; Choi, Kang-Ho; Kim, Munki; Kim, Jahae
Abstract : BACKGROUND: Gamma probes can provide real-time information on lesion location and allow radioguided surgery in many diseases. The purpose of this study was to determine whether a gamma probe could be used to confirm balloon location in resuscitative endovascular balloon occlusion of the aorta and to determine the ease-of-use of the gamma probe localization method using human vasculature phantom and large animal. METHODS: This investigation comprised a proof-of-concept study using human vasculature phantom and feasibility study using large animal. An assistant and two general surgeons with no prior experience in handling a gamma probe participated in both studies. A gamma probe was used by each surgeon to explore the location of a catheter balloon filled with 8 mL of normal saline containing 37 MBq of 99m Technetium. The differences between predicted and actual balloon locations and the times taken to perform the trials were recorded. Balloon locations were confirmed by planar gamma camera images. The results were analyzed and compared according to the operators and experiments. RESULTS: Overall sensitivity and specificity for the localization of the catheter balloon were 100% and 91% in phantom study, respectively, and 100% and 100% in animal study, respectively. The performance of the two operators for exploring the balloon location was similar in both the phantom and the animal studies. The mean time taken to explore the balloon locations with the aid of the gamma probe was only 2.36 minutes in phantom study and 2.65 minutes in the animal study. CONCLUSION: The gamma probe method was accurate and rapid for confirming balloon location. We suggest that the gamma probe has potential for confirming balloon placement in endovascular procedures without the need for fluoroscopy.